2005
DOI: 10.2136/sssaj2005.0029
|View full text |Cite
|
Sign up to set email alerts
|

Restoration and Canopy Type Influence Soil Microflora in a Ponderosa Pine Forest

Abstract: species. The risk of stand-replacing fire has also greatly increased due to heavy fuel loading and high tree den-In ponderosa pine (Pinus ponderosa Dougl. ex Laws.) forests of sity, threatening local plant and animal life (Covington the western USA, fire exclusion by Euro-American settlers facilitated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 61 publications
2
27
1
1
Order By: Relevance
“…As alterações nessas enzimas nas diferentes coberturas vegetais podem ser explicadas pelo fato de elas atuarem na degradação de carboidratos do solo; a β-glucosidase atua na hidrólise de maltose e celubiose e a β-galactosidase pela hidrólise de melibiose e lactose, os quais são importantes fontes de energia metabólica para microbiota do solo (Eivazi & Tabatabai, 1988;Boyle et al, 2005). A arilsulfatase, por estar presente em fungos na forma de ésteres sulfatos, também participa como componente da formação da biomassa microbiana do solo (Bandick & Dick, 1999).…”
Section: Resultsunclassified
“…As alterações nessas enzimas nas diferentes coberturas vegetais podem ser explicadas pelo fato de elas atuarem na degradação de carboidratos do solo; a β-glucosidase atua na hidrólise de maltose e celubiose e a β-galactosidase pela hidrólise de melibiose e lactose, os quais são importantes fontes de energia metabólica para microbiota do solo (Eivazi & Tabatabai, 1988;Boyle et al, 2005). A arilsulfatase, por estar presente em fungos na forma de ésteres sulfatos, também participa como componente da formação da biomassa microbiana do solo (Bandick & Dick, 1999).…”
Section: Resultsunclassified
“…Thinning only did not alter our microbial populations in either the forest floor or mineral soil, and there was no effect on microbial activities we measured. Boyle et al [74] also found little evidence of thinning impacts on microorganisms in mineral soil from the same study site used by Kaye and colleagues [21]. Microbial response to thinning in other forest types has been shown to be quite variable, from reduced microbial biomass without altering the population structure [44], to structural differences without altering microbial biomass [75][76][77], to altered biomass and structure [78].…”
Section: Discussionmentioning
confidence: 96%
“…A meta-analysis by Johnson and Curtis [80] concluded that changes in total mineral soil C and N contents in coniferous stands following thinning were the result of harvest method and treatment of residues. Total C and N contents in the mineral soil have initially been unaffected following restoration treatments that included thinning and prescribed fire in other ponderosa pine stands in northern Arizona [6,79], but long-term increases in total soil N have also been reported [31,74]. The limited effects of the FFS thinning treatments are due in part to modest stand density reductions from a single application.…”
Section: Discussionmentioning
confidence: 99%
“…The tree removal increases insolation to the ground and changes soil water regime by altering the rates of evaporation and transpiration, and eliminating interception of precipitation by the canopy. These relatively immediate changes in soil microclimate may directly alter the composition and the activity of the soil microflora (Boyle et al 2005). On the other hand, retaining of fallen trees and coarse woody debris on the plot also leads to changes in ecological conditions as the fallen trees shadows affect the water and temperature regimes, and there is a considerable amount of organic material lying on the ground and gradually decomposing.…”
Section: Soil and Water Res 3 2008 (Special Issue 1): S74-s80 Originmentioning
confidence: 99%